PERKECAMBAHAN DAN PERTUMBUHAN AWAL BUDSET DAN BUDCHIP TEBU (Saccharum officinarum L.) YANG DITANAM PADA BERBAGAI POSISI MATA TUNAS - Rivandi Pranandita Putra (Jurnal Agrotek Tropika, 2020)
Germination phase is a crucial stage in the cultivation of sugarcane. This phase is influenced by numerous factors, such as the position of bud when the sugarcane seed is planted. This study aims to examine the responses of germination and early growth of sugarcane bud chip and budset seeds variety PS 862 that are grown in various bud positions, namely upward, downward, and side positions. Results explicated that there were significant differences in the seed germination that are grown with various bud positions. Seeds that are planted with a downward bud position germinate slower than the two other bud positions. However, the percentage of germination of all treatments were classified as vigorous since the numbers are more than 80%. There was a strong influence of the bud position on the number of tillers and root/shoot ratio. Seeds that are planted with upward and side bud position have more tillers than seeds grown with the two other positions. The root/shoot ratio was higher in seeds grown with upward positions than the other positions. Meanwhile, there were no significant effects of bud positions and the form of seed on plant and stem height, the number of leaves, as well as root, shoot, and total dry weight of the crop.